Non-orthogonal Multiple Access: An Enabler for Massive Connectivity - Bhatia V.; Swami P.; Sharma S.; Mitra R. (My University, 2025)
Two of the most challenging goals for the fifth generation (5G) and beyond communication systems are massive connectivity and higher capacity. The use of traditional orthogonal multiple access techniques limits the number of users that can be served using available resources due to orthogonality constraint. Moreover, the available resources may not be utilized effectively by alloted users thereby resulting in inefficiency and user unfairness. This imposes a severe drawback in cases where the number of users to be served are high, like in the Internet of Things or ultra-dense 5G networks. Hence, introducing non-orthogonality to multiple access scheme is advocated as a superior methodology to serve multiple users simultaneously, thereby achieving multi-fold enhancement in connectivity. In scenarios with massive number of users, non-orthogonal multiple access scheme (NOMA) increases the number of active connections by superimposing signals of multiple users on the same resource block, thereby also utilizing the available resources efficiently. This article presents an overview of the integration of NOMA with several other leading technologies for 5G and beyond networks to enhance the connectivity. © 2020, Indian Institute of Science.